A history of capitalist transformation : a critique of liberal-capitalist reforms - Conte, Giampaolo (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"A History of Capitalist Transformation: A Critique of Liberal-Capitalist Reforms highlights how, since the recent financial crises, the expression 'liberal reform' has entered common parlance as an evocative image of austerity and economic malaise, especially for the working classes and a segment of the middle class. But what exactly does 'liberal reform' refer to? The research analyses the historical origins of liberal-capitalist reformism using a critical approach, starting with the origins of the Industrial Revolution. The book demonstrates that the chief purpose of such reforms was to integrate semi-peripheral states into the capitalist world-economy by imposing, both directly and indirectly, the adoption of rules, institutions, attitudes, and procedures amenable to economic and political interests of capitalist élites and hegemonic states - Britain first, the United States later - between the nineteenth and twenty-first centuries. As such, the reforms became an active tool used to promote social-economical-financial institutions, norms, and lifestyles typical of a liberal-capitalist economic order, which locates some of its founding values in capital accumulation, profit-seeking, and social transformation. This book will be of significant interest to readers on capitalism, political economy, the history of the global economy and British history"--
Keywords: Liberalism; Capitalism; Liberalism -- Great Britain; Capitalism -- Great Britain; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / Theory